2013
DOI: 10.1136/bmjspcare-2013-000491.56
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Advance Care Planning for Renal Patients

Abstract: Background Research indicates that renal patients are uninformed about care options and have limited knowledge about illness prognosis and trajectories. Accordingly, facilitated Advance Care Planning (ACP) was introduced to the renal unit at the Austin Hospital in 2010. Aim To evaluate the impact of the introduction of ACP to the Austin Hospital renal unit. Methods Audit of medical records for (1) 58 patients who received ACP (2010-2012) (2) 58 age and gender matched control patients (2007-2009). Results The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Work in this area is limited, but a study by Silvester et al . () found that the implementation of ACP enabled the documentation and respecting of patients wishes and more patients receiving treatments that were in their best interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in this area is limited, but a study by Silvester et al . () found that the implementation of ACP enabled the documentation and respecting of patients wishes and more patients receiving treatments that were in their best interest.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should include identifying the place of death of patients who die in and out of hospital and whether or not the death was expected. Silvester et al (2013) found that the implementation of ACP enabled the documentation and respecting of patients wishes and more patients receiving treatments that were in their best interest.…”
Section: Discussionmentioning
confidence: 99%